2019
DOI: 10.1016/j.chest.2019.08.1396
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Midodrine on Duration of Vasopressor Infusion in Patents With Septic Shock in a Community Hospital Setting

Abstract: Vasopressor infusions are commonly used for hemodynamic support in the intensive care unit, especially in patients with septic shock and refractory hypotension. The duration of IV vasopressors is variable and often require careful and specialized monitoring by highly skilled critical care staff. Midodrine, as a pure alpha 1 agonist, has been shown to shorten the time septic shock patients need to be on vasopressor support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous retrospective studies and one RCT have been conducted with conflicting results; some showed that midodrine is helpful in this process [ 13 , 14 , 17 , 19 ], and others including the RCT showed no benefit of adding midodrine to facilitate weaning off IVV [ 6 , 15 , 18 ]. Surprisingly, two studies showed that midodrine increases hospital and ICU LOS [ 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous retrospective studies and one RCT have been conducted with conflicting results; some showed that midodrine is helpful in this process [ 13 , 14 , 17 , 19 ], and others including the RCT showed no benefit of adding midodrine to facilitate weaning off IVV [ 6 , 15 , 18 ]. Surprisingly, two studies showed that midodrine increases hospital and ICU LOS [ 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the prior studies reviewed, Whitson et al [ 13 ], Hailu et al [ 17 ], Liu et al [ 14 ], and Nadhim et al [ 15 ] were the only ones that included patients with septic shock. Whitson et al [ 13 ], Liu et al [ 14 ] (abstract), and Hailu et al [ 17 ] (abstract) showed a significant reduction in IVV duration, ICU LOS, and Hospital LOS while Nadhim et al [ 15 ] (abstract) did not show a significant decrease in IVV duration. Analysis limited to studies that included patients with septic shock was not done as 3 of these studies are just published as abstracts and did not report standard deviations for means or interquartile ranges for medians to pool them in our quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine is still the first-line agent for vasoplegia, but it requires continuous ICU monitoring that leads to prolonged ICU stays [ 6 ]. A lot of interest has been directed towards using midodrine, an oral alpha-1 agonist, in patients with resolving shock who remain vasopressor-dependent, with the goal of liberating patients from IV pressors [ 18 – 22 ]. Midodrine is approved for the treatment of a variety of conditions, including orthostatic hypotension, neurogenic hypotension [ 11 ], and hypotension caused by carotid artery stenting [ 23 ].…”
Section: Discussionmentioning
confidence: 99%